Preparation and evaluation of nanocellulose–gold nanoparticle nanocomposites for SERS applications1. Issue 16 (21st August 2015) - Wei, Haoran; Rodriguez, Katia; Renneckar, Scott; Leng, Weinan; Vikesland, Peter J.
<x xml:space="preserve">Abstract</x> We present a gold nanoparticle/bacterial cellulose nanocomposite SERS substrate that accumulates analytes in hydrogel form and then exhibits strong Raman signal enhancements after drying.